Nutrient intake and dental health in school children - (:unkn) unknown (My University, 1996)
Diet refers to the customary allowance of food and drink taken by a person from day to day. The diet may affect dental caries by reacting with the enamel surface and by serving as a substrate for cariogenic microorganisms. This study examined the role of specific nutrients in the caries experience of elementary school children. 120 children aged between 6-11, who attended the Pedodontics Department of Marmara University, Faculty of Dentistry for routine dental treatment received a dental examination, parent interview, and a 3-day diet diary. The diary was completed adequately for 100 children (83%). The average daily intake of nutrients were computed and total sugar consumption and Ca/P ratio were calculated. Each child's gender, age, fluoride history, socio-economic state of the family, previous dental experience, brushing habit, and nutrient intake were examined as independent variables. No association was apparent between dental caries and the intake of specific nutrients or Ca/P ratio, except with total sugar consumption.
Keywords: Female; Humans; Turkey; Male; Child; Oral Health; Toothbrushing; Analysis of Variance; Dental Caries Susceptibility; DMF Index; Feeding Behavior; Diet Surveys; Nutritional Status